A Semiotic Analysis on FIFA World Cup 2022 Qatar Memes - Amos Ruben Panjaitan; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Memes have become a unique way of conveying messages and sharing experiences in today's social media era. The FIFA World Cup is one of the biggest sporting tournaments in the world, and its audience, which is divided into various regions and circles, has attracted researchers to make it an object. The aims of this semiotic analysis study are to determine the signifier and the signified, as well as the denotation and connotation, as well as the meaning of FIFA World Cup Qatar 2022 memes. The descriptive qualitative method is being used in the study. To analyze the data, the researchers applied Roland Barthes' theory. Memes are classified as signifiers and signified, which can be expressed verbally or visually. The researchers also explained the denotative and connotative interpretations of the 2022 FIFA World Cup in Qatar. The writers selected four memes for this analysis that talked about watching experiences, trolling the fans and players, and giving thoughts about the FIFA World Cup 2022 Qatar tournament. The results show that the signifiers in the memes were very random and unique, such as the heartbeat display in the first image, scientists in the second image, actors in the third image, scientists, and cartoon characters with flags in the last image. These signs certainly have objective or literal meanings (denotation) and subjective or other meanings (connotation).Â  Most of the connotational meaning from memes that have been analyzed focuses on sharing the experience of watching the FIFA World Cup 2022 competition and also trolling the football supporters or even the players that participated